Short total synthesis of (+)-cryptocarya diacetate - Gurjar, Mukund K.; Raghupathi, Neelarapu; Chorghade, Mukund S. (Heterocycles, 2009)
A short synthesis of (+)-cryptocarya diacetate was achieved by employing three component linchpin coupling, diastereoselective reduction of beta-hydroxyketone, and Z-selective HWE reaction as key transformations.
Keywords: Brook Rearrangement; cryptocarya diacetate; Diastereoselective Reduction; Horner-Wadswarth-Emmons Reaction; Linchpin coupling

Synthesis of aculeatins A and B via iterative hydrolytic kinetic resolution - Harbindu, Anand; Kumar, Pradeep (Synthesis-Stuttgart, 2010)
A simple and concise approach for the synthesis of aculeatins A and B starting from (+/-)-epichlorohydrin is described. The synthetic strategy features Jacobsen's hydrolytic kinetic resolution and a Linchpin coupling as key steps.
Keywords: aculeatins; Epoxide; Hydrolytic kinetic resolution; Linchpin coupling; spirocyclization